Calculer les expressions en détaillant les calculs.

A= [-5 - (-8)] x (-2)
B= 26 - (-9) x 1,5 - 0,5
C= 26 : ( - 3 - 2 x 5)

2
A=13x(-2)
A= -26
-5-(-8) ça fait -5+8
B= 26-(-13.5)-0.5
B=39.5-0.5
B=39
oups jme suis tromper sur le A c'est

A=3x(-2)
A= -6
C=26:(-3-4)
C=26:1
C=26

Réponses

2013-10-28T13:57:43+01:00
A = [-5-(-8)]x(-2)
   = (-5+8)x(-2)
   =3x(-2)=-6
B = 26-(-9)x1,5-0,5
   = 26-(-13,5)-0,5
   = 26+13,5-0,5=39
C = 26 : (-3-2x5)
   = 26:(-3-10)
   = 26:(-13)=-2
2013-10-28T14:13:31+01:00
Bonjour

A= [-5 - (-8)] x (-2)
A = (-5+8) x -2
A = 3 x -2
A = -6

B= 26 - (-9) x 1,5 - 0,5
B = 26 - (-13.5) -0.5
B = 26 +13.5 -0.5
B = 39.5 -0.5
B = 39

C= 26 : ( - 3 - 2 x 5)

C = 26 : (-3 -10)
C = 26 : -13
C = -2